(untitled) (Journal of Nepal Geological Society, 1999)
In-situ testing of rock mechanical parameters is essential for rock mass characterisation. The rock mass characterisation is important in design and construction of underground works forming major component of Hydropower projects. The major civil structures of most of the hydropower projects planned in Nepal have to be founded on complex rock formations on fragile geological environments. In-situ rock mechanics tests carried out at various hydropower projects sites are described and the findings are summarised.